Power Tiller Requirement for Cassava Cultivation at Estate Scale - Rufiani Nadzirah; Agus Dharmawan; Siswoyo Soekarno; Indarto Indarto; Tasliman Tasliman (The University of Lampung, 2022)
Indonesia's food needs continue to increase along with population growth. Land development for supporting the cassava food estate is one of the priority programs of the central and regional governments. The purpose of this study was aimed at determining the need for power tiller for land management based on land area. This research was carried out at the planned location of the cassava plantation in Gunung Mas Regency, Central Kalimantan in 2020. The data on the land area planned was determined from a topographic map, while the tractor needs were obtained from the calculation of field capacity. The area of land suitable for cassava cultivation is 1227.57 ha which is divided into 25 blocks. The basis for the number of tractors as power tiller needed is determined from the time of tillage work so that it requires working capacity variables, including data on land area, work speed, and width of the plow implement. The plow studied in this study used 2, 3, 4, and 5 blades of disc plows. The need for a tractor with a 5-blade disc plow is 2 tractors that work fully and take turns cultivating an area of 1227.57 ha in the span of one cassava cultivation period (7-8 months). If the disc plow used is less than five blades, it will affect the working width of tillage, so the work time will be longer and the need for power tiller will increase. Keywords: Cassava, Disk Plow, Food Estate, Power Tiller, Tractor